An introduction to Japanese society - Sugimoto, Yoshio 1939- (Cambridge Univ. Press, 2014)
This revised edition has been updated to cover developments in the five years since the first edition was published. Yoshio Sugimoto challenges the traditional notion that Japan is an homogeneous society with few cultural and social disparities.